PENINGKATAN PENGETAHUAN MASYARAKAT TENTANG PERILAKU HIDUP BERSIH DAN SEHAT MELALUI EDUKASI DAN PELATIHAN - Dimas Pramita Nugraha; Afdal Afdal; Eka Bebasari (Komunitas Manajemen Kompetitif, 2026)
Abstract: Low levels of public knowledge and awareness regarding clean and healthy living practices lead to high rates of illness and a decline in quality of life. Therefore, efforts are needed to improve public knowledge about clean and healthy living practices. The objective of this community service program is to enhance public knowledge regarding clean and healthy living practices. The program was implemented in Kuala Terusan Village, Pangkalan Kerinci Subdistrict, Pelalawan Regency, Riau Province. The methods used were education on clean and healthy living practices and training on proper handwashing techniques in accordance with World Health Organization standards. An evaluation of the community’s knowledge level was conducted by comparing pre-test results before the education session with post-test results after the education session. The results showed that the proportion of the community with good knowledge increased from 5.89% in the pre-test to 60% in post-test after the education and training were provided. These results demonstrate that the education and training methods were sufficiently effective in improving the community’s knowledge regarding clean and healthy living practices. Continuous education and training on clean and healthy living practices are a crucial solution to help the community recognize the importance of adopting such behaviors in their environment.